Screening and hit evaluation of a microbial metabolite library against the pathogenic Plasmodium falciparum and Toxoplasma gondii parasites - Maria R. Gancheva; Emma Y. Mao; Ornella Romeo; Daniel Vuong; Ryan O'Handley; Stephen W. Page; Ernest Lacey; Danny W. Wilson (International Journal for Parasitology: Drugs and Drug Resistance)
Frontline drug treatments for malaria are at risk of failing due to emerging resistance, meanwhile drugs used to treat toxoplasmosis have suboptimal efficacy and safety. As demonstrated by the success of clinically used antiparasitic drugs, the diverse structural complexity and biological activity of natural products holds great potential for drug discovery and development, to address the need for new compounds with novel mechanisms. Here we screened the BioAustralis Discovery Plates Series I library, a collection of 812 microbial natural product compounds including rare microbial metabolites, against Plasmodium falciparum erythrocytic stage and Toxoplasma gondii tachyzoite parasites. We identified 219 compounds that inhibited P. falciparum growth by at least 80 % at a concentration of 2 μg/mL (1–10 μM for >90 % of compounds), whilst 149 compounds demonstrated equivalent activity against T. gondii. The active compounds were assigned based on chemical structure to more than 50 compound classes. After triaging active compounds for those with low mammalian cytotoxicity, we defined the in vitro half maximal inhibitory concentration (IC50) of a selection of compounds against the parasites, identifying four compound groups with activity in the low nanomolar range. The macrocyclic lactone pladienolide B and cryptopleurine were found to be very potent against the parasites but also mammalian cells, warranting further structure-activity relationship investigation. Two groups, the monocyclic thiazole peptides, including micrococcin P1 and the thiocillins, and the pleuromutilins, exhibited both low antiparasitic IC50 and low cytotoxicity, highlighting their potential for further analysis. This study defines the activity of the BioAustralis Discovery Plates Series I against two apicomplexan parasites of significant global importance, providing potential new tools to study parasite biology and possible starting points for novel antiparasitic development.